Exogenous Application of Gallic Acid Induces the Direct Defense of Tea Plant Against Ectropis obliqua Caterpillars - Zhang, Xin; Ran, Wei; Li, Xiwang; Zhang, Jin; Ye, Meng; Lin, Songbo; Liu, Miaomiao; Sun, Xiaoling (Frontiers in Plant Science, 2022)
Gallic acid (GA), an important polyphenolic compound in the plant, is a well-known antioxidant, antihyperglycemic, and anti-lipid peroxidative agent. Recently, GA treatment exhibited ameliorative effects on plants in response to some abiotic stresses. However, the elicitation effect of GA on plant defense against herbivorous insects has not yet been reported. In this study, we found that the exogenous application of GA induced the direct defense of tea plant (Camellia sinensis) against tea geometrid (Ectropis obliqua) larvae, through activating jasmonic acid (JA) signaling and phenylpropanoid pathways. These signaling cascades resulted in the efficient induction of several defensive compounds. Among them, astragalin, naringenin, and epigallocatechin-3-gallate were the three of the most active anti-feeding compounds. However, the exogenous GA treatment did not affect the preference of E. obliqua female moths and larval parasitoid Apanteles sp. Our study suggests that GA may serve as an elicitor that triggers a direct defense response against tea geometrid larvae in tea plants. This study will help to deepen the understanding of the interaction between plants and phytophagous insects and also provide theoretical and technical guidance for the development of plant defense elicitors.